2016
DOI: 10.5194/acp-16-8729-2016
|View full text |Cite
|
Sign up to set email alerts
|

Model–measurement comparison of functional group abundance in <i>α</i>-pinene and 1,3,5-trimethylbenzene secondary organic aerosol formation

Abstract: Abstract. Secondary organic aerosol (SOA) formed by α-pinene and 1,3,5-trimethylbenzene photooxidation under different NOx regimes is simulated using the Master Chemical Mechanism v3.2 (MCM) coupled with an absorptive gas–particle partitioning module. Vapor pressures for individual compounds are estimated with the SIMPOL.1 group contribution model for determining apportionment of reaction products to each phase. We apply chemoinformatic tools to harvest functional group (FG) composition from the simulations an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 126 publications
(185 reference statements)
3
10
0
Order By: Relevance
“…The chemical mechanism used in Browne et al (2013) and Zare et al (2018) are based on the Master Chemical Mechanism (MCM) that is well known in the degradation chemistry of VOC in the gas phase (Jenkin et al, 1997;Saunders et al, 2003). However, the same mechanism performs poorly in regards to the chemical composition of SOA (Faxon et al, 2018) as well as the prediction of SOA formation (Ruggeri et al, 2016;Boyd et al, 2017) when equipped with gasparticle partitioning modules based on the absorptive gas-particle partitioning theory (Pankow, 1994). It is, therefore, reasonable to argue that the chemical composition of pON could greatly differ from that of total ON predicted by the MCM.…”
Section: Hydrolyzable Fraction Of Particulate Organic Nitratementioning
confidence: 99%
“…The chemical mechanism used in Browne et al (2013) and Zare et al (2018) are based on the Master Chemical Mechanism (MCM) that is well known in the degradation chemistry of VOC in the gas phase (Jenkin et al, 1997;Saunders et al, 2003). However, the same mechanism performs poorly in regards to the chemical composition of SOA (Faxon et al, 2018) as well as the prediction of SOA formation (Ruggeri et al, 2016;Boyd et al, 2017) when equipped with gasparticle partitioning modules based on the absorptive gas-particle partitioning theory (Pankow, 1994). It is, therefore, reasonable to argue that the chemical composition of pON could greatly differ from that of total ON predicted by the MCM.…”
Section: Hydrolyzable Fraction Of Particulate Organic Nitratementioning
confidence: 99%
“…Further, ON and HNO 3 can be removed via dry and wet deposition. One important reaction of ON in the particle phase is hydrolysis in the presence of aerosol water, which is a mechanism for NO x loss (Day et al, 2010;Russell et al, 2011). Studies with bulk solutions showed that particlephase hydrolysis of tertiary nitrate is fast with a lifetime of minutes, while primary and secondary nitrate is stable (Darer et al, 2011;Hu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…No experimental data are available for the ambient concentrations of organic compounds belonging to Clusters 7 or 8. However, SOA modelling studies indicate that they can account for a significant fraction of SOA mass formed by substituted benzene oxidation (Ruggeri et al, 2016), which translates into ambient concentrations of several ng m −3 in very polluted environments (such as in Yuan et al, 2013; Table S10). The formation of endoperoxides and epoxides and of other reactive oxygenated organic compounds, such as those in Clusters 7 and 8, was hypothesized by Fu et al (2012) to explain the DNA damage caused by photodegraded aromatic compounds.…”
Section: Cluster Analysismentioning
confidence: 99%